Model Penguatan Daya Saing sebagai Upaya Peningkatkan Kinerja Bisnis UKM Klaster Mebel di Jepara - Sisno Riyoko; Budi Lofian (Jurusan Manajemen Fakultas Ekonomi Universitas Sriwijaya, 2020)
This study wants to produce a model of strengthening competitiveness is a form of model with attention to the determinants of competitiveness. The purpose of this study is to further enhance the competitiveness of SMEs in the form of training and strengthening of target SMEs. Other research objectives are 1) description of characteristics of SME Furniture cluster, 2) Establishment of a model of strengthening competitiveness that can be applied proaktis, 3) teraplikasikanya model empirically and 4) terujinya application model of competitiveness strengthening. To achieve tujan is done method of action reseach approach, that is research activity followed by implementation. Stages of activities to be undertaken are: 1) identification of SMEs with survey, desk analysis and focus group discution; 2) formulating a model of strengthening competitiveness by descriptive method; 30 formulating and applying competitiveness strengthening model and implementation guide; and 4) testing model implementation strengthening competitiveness and revising the final model. The results of research activities that have been conducted in the first year are identified characteristics of SMEs include business ownership, origin of capital, total assets, number of employees, employee education, length of standing business, marketing area and production system. While the analysis of the strengths and weaknesses of SMEs is as follows SMEs have a potential product for market acceptance, have a good relationship with customers, have a product innovation, easy to get human resources. in terms of weakness of SMEs still rely on their own capital, network pemasarn still low, human resource skills need to be improved. From the analysis, a strengthening model is created by providing training and business assistance. so that in the second year implementation model can be implemented so that the performance of SMEs can increase.